2022
DOI: 10.3390/vaccines10020237
|View full text |Cite
|
Sign up to set email alerts
|

The Attitude towards Vaccination of Health Sciences Students at a Spanish University Improved over the First 18 Months of the COVID-19 Pandemic

Abstract: It is important to know the attitudes of students of health sciences (SHSs) towards vaccination since they will be tomorrow’s health professionals. Vaccination is a powerful tool in the fight against COVID-19. The aim of the present, cross-sectional study was to examine how the COVID-19 pandemic has influenced the attitude of SHSs towards vaccination. Data were collected in the form of a questionnaire from all students of nursing, physiotherapy and chiropody matriculated at a Madrid University for the academic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 55 publications
(58 reference statements)
2
12
0
Order By: Relevance
“…According to our findings, the rate of resident doctors who adhered to the COVID-19 vaccination programme is close to 100%; in fact, only 0.26% of them did not receive a vaccination. These results show a very high compliance rate of MRs towards compulsory vaccination even compared to studies performed in other states [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 49%
“…According to our findings, the rate of resident doctors who adhered to the COVID-19 vaccination programme is close to 100%; in fact, only 0.26% of them did not receive a vaccination. These results show a very high compliance rate of MRs towards compulsory vaccination even compared to studies performed in other states [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 49%
“…The current study did not find any correlation between HCWs different demographics and vaccine acceptance, however, those who had been previously infected with COVID-19 were more likely to support vaccination against Monkeypox. A previous study from KSA that examined factors related to COVID-19 vaccine acceptance among HCWs prior to its availability did not show higher acceptance among previously infected individuals with COVID-19, but probably after 2 years of the pandemic and experiencing the protection effect of vaccination campaigns, HCWs felt more encouraged toward Monkeypox vaccination with increasing confidence in vaccination in general, this was observed with Flu vaccine during COVID-19 pandemic and vaccination in general[32-34]. Interestingly, HCWs who advocated for tighter infection-prevention and control measures were also more supportive of vaccination, both in line with their healthy behavior and their belief that both are integral to each other, this echoes a previous study that showed higher rate of hepatitis B vaccination in HCWs who attended infection control training[35].…”
Section: Discussionmentioning
confidence: 94%
“…This finding was not surprising as COVID-19 pandemic affected medical students more and even raised their concerns to reconsider their profession [25]. HCWs who previously pandemic and vaccination in general [32][33][34]. Interestingly, HCWs who advocated for tighter infection-prevention and control measures were also more supportive of vaccination, both in line with their healthy behavior and their belief that both are integral to each other, this echoes a previous study that showed higher rate of hepatitis B vaccination in HCWs who attended infection control training [35].…”
Section: Discussionmentioning
confidence: 99%
“…All enrolled students, regardless of year, were invited to complete the Scale of "Attitudes and Behaviors in Relation to Vaccination among Students of Health Sciences" (ACVECS-according to its Spanish initials) [10]), previously translated by two translators, which resulted in an overlapping translation. The ACVECS scale, which aims to measure health students' attitudes and behaviors with regard to vaccination, is made up of 24 items, the first 15 of which measure the "attitudes" dimension and the last 9, "behaviors" [10][11][12][13]. These 24 items were answered on a five-point Likert-type scale, ranging from 0 = strongly disagree to 4 = strongly agree.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the issue of health promotion to be of the utmost importance, mainly in the sequence of experiences experienced in the current context, and following studies carried out in Spain [10][11][12][13], the objective of the study was to analyze the attitudes and behaviors of nursing students in the face of vaccination, but within the particularities of the Portuguese context. Regarding particular objectives, the aim is to: determine influenza and COVID-19 vaccination coverage in a sample of nursing students; identify characteristics related to this vaccination coverage; and correlate attitudes and behaviors with regard to vaccination with age, gender, and year of study.…”
Section: Introductionmentioning
confidence: 99%